Dietary supplements for athletic performance in women: beta-alanine, caffeine, and nitrate - Murphy, M. J.; Rushing, B. R.; Sumner, S. J.; Hackney, A. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Beta-alanine, caffeine, and nitrate are dietary supplements generally recognized by the sport and exercise science community as evidence-based ergogenic performance aids. Evidence supporting the efficacy of these supplements, however, is greatly skewed due to research being conducted primarily in men. The physiological differences between men and women, most notably in sex hormones and menstrual cycle fluctuations, make generalizing male data to the female athlete inappropriate, and potentially harmful to women. This narrative review outlines the studies conducted in women regarding the efficacy of beta-alanine, caffeine, and nitrate supplementation for performance enhancement. Only nine studies on beta-alanine, 15 on caffeine, and 10 on nitrate in healthy women under the age of 40 years conducted in normoxia conditions were identified as relevant to this research question. Evidence suggests that beta-alanine may lower the rate of perceived exertion and extend training bouts in women, leading to greater functional adaptations. Studies of caffeine in women suggest the physiological responder status and caffeine habituation may contribute to caffeine`s efficacy, with a potential plateau in the dose-response relationship of performance enhancement. Nitrate appears to vary in influence based on activity type and primary muscle group examined. However, the results summarized in the limited literature for each of these three supplements provide no consensus on dosage, timing, or efficacy for women. Furthermore, the literature lacks considerations for hormonal status and its role in metabolism. This gap in sex-based knowledge necessitates further research on these ergogenic supplements in women with greater considerations for the effects of hormonal status.